PERSEPSI TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Uli. S, Desti Monika; Pirmansyah, Pirmansyah; Wahyu, Wadri; Munika, Rani; Oktaviani, Wulan (Jurnal Akuntansi Kompetif, 2025)
This study aims to determine the effect of perceptions of tax rates, service quality, and tax knowledge on tax compliance for micro small and medium businesses. This study also deals with the phenomenon of reducing the tax rate of micro small and medium enterprises to zero point five percent. The object of study was the taxpayer of small and medium business in Kampar Regency. The sample used was 158 small and medium micro business taxpayers who were selected using a simple random sampling technique.The study was conducted using primary data through a questionnaire with data analysis through the Structural Equation Model (SEM) approach based on Partial Least Square (PLS) with the WarpPLS 3.0 application program. The results of direct influence testing show that perceptions of tax rates, service quality and tax knowledge affect tax compliance for small and medium micro business taxpayers